Compounding in Danish - Krasnova, Elena (Scandinavistica Vilnensis, 2014)
Compounding is a major word formation process in Danish. Approaches currently important for examining Danish compounds are outlined, mostly based on two-constituent N+N compounds. We argue that compounding has both specific and universal features in different languages. Different types of compounds in Danish are discussed with focus on elliptical compounds, without direct semantic relations between the components. This comprehensive approach has proved useful as compounds in Danish differ considerably in semantic relations between the components. The experiment shows that for some groups of “popular” words, analogy plays a great role in the creation and interpretation of novel compounds.